Endocrine-disruptor endpoints in the ovary and thyroid of adult female rats exposed to realistic doses of di-(2-ethylhexyl) phthalate - Jebara, Amel; Beltifa, Asma; Di Bella, Guissepa; Mabrouk, Lotfi; Ben Mansour, Hedi (Journal of water and health, 2022)
Di-(2-ethylhexyl) phthalate (DEHP) is the world's most widely used polyvinyl chloride (PVC) plasticizer and is used in virtually every category of flexible PVC. In fact, DEHP is extensively used in food cosmetics and medical packaging. It has become a serious problem in recent years. DEHP can be absorbed into the human body through the air, food, water, and skin. The current study involved intraperitoneal injection of DEHP dissolved in corn oil once daily for 21 consecutive days to investigate the effects of DEHP on the thyroid and the reproductive system in female rats. Results show that ovarian hormones (progesterone and estrogen) decreased significantly in the rats treated with DEHP compared to control. This result is supported by the alteration of folliculogenesis, the decrease of the follicles viability, and the apoptosis of the granulosa cells observed on histological sections of ovary and thyroid in female rats exposed to low doses of DEHP. Histopathological study revealed that DEHP could damage thyroid tissue and disrupt these functions. We also observed cellular damage, particularly in the liver cells, and a significant increase in biochemical parameters such as alanine aminotransferase (ALT) and aspartate aminotransferase (AST) compared to the control group.